ЗАРАРЛИ КЕМИРУВЧИЛАР БИЛАН КУРАШИШНИНГ ЭКОЛОГИК АСОСЛАРИ - Утенова, Г.У.; Узакбергенов, А.Ж. (SCIENCE and SOCIETY, 2023)
The article presents the ecological basis of the control of the most common harmful rodents in the agro-landscape zone of Qorakalpakistan. In this study, several measures that were used between 1950 and 1966 are presented. Based on the results of the accumulated experience, the development and application of a modern effective method of combating harmful rodents that does not harm other fauna is a scientific problem facing this field.